2016
DOI: 10.1074/jbc.m115.704494
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae Forms d-2-Hydroxyglutarate and Couples Its Degradation to d-Lactate Formation via a Cytosolic Transhydrogenase

Abstract: The D or L form of 2-hydroxyglutarate (2HG) accumulates in certain rare neurometabolic disorders, and high D-2-hydroxyglutarate (D-2HG) levels are also found in several types of cancer. Although 2HG has been detected in Saccharomyces cerevisiae, its metabolism in yeast has remained largely unexplored. Here, we show that S. cerevisiae actively forms the D enantiomer of 2HG. Accordingly, the S. cerevisiae genome encodes two homologs of the human D-2HG dehydrogenase: Dld2, which, as its human homolog, is a mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
122
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(136 citation statements)
references
References 82 publications
13
122
1
Order By: Relevance
“…D2-HG levels in wild-type strains ranged between 10 and 60 µM, in agreement with previous levels measured in yeast (Becker-Kettern et al, 2016). Consistent with a role in metabolizing D2-HG, a dld2∆ mutation led to a ~50 fold increase in cellular D2-HG levels in cells grown on glycerol (Figure 3A) and a fivefold increase in cells grown on glucose (Figure 3D).…”
Section: Resultssupporting
confidence: 90%
“…D2-HG levels in wild-type strains ranged between 10 and 60 µM, in agreement with previous levels measured in yeast (Becker-Kettern et al, 2016). Consistent with a role in metabolizing D2-HG, a dld2∆ mutation led to a ~50 fold increase in cellular D2-HG levels in cells grown on glycerol (Figure 3A) and a fivefold increase in cells grown on glucose (Figure 3D).…”
Section: Resultssupporting
confidence: 90%
“…As previously reported by Becker-Kettern et al [16], steadystate experiments revealed a higher catalytic efficiency and lower K Mapp with D-a-hydroxyglutarate, but also a lower turnover. As previously reported by Becker-Kettern et al [16], steadystate experiments revealed a higher catalytic efficiency and lower K Mapp with D-a-hydroxyglutarate, but also a lower turnover.…”
Section: Introductionsupporting
confidence: 85%
“…Strains are in the W303 background, and cell dilutions match those in Figure 1C. We note that annotations of DLD2 and DLD3 as D-lactate dehydrogenases have recently been challenged by data suggesting they are instead transhydrogenases (Becker-Kettern et al, 2016). Only DLD1 is required for yeast to grow on D-lactic acid as a sole carbon source.…”
Section: Resultsmentioning
confidence: 73%